Meta-Analysis: Effect of Breastfeeding Education Program on the Breastfeeding Self-Efficacy and Exclusive Breastfeeding - Annisa Nurindra Rahmadani; Anisya Fajar Rahmawati (Journal of Health Promotion and Behavior, 2022)
Background: Improving self-efficacy in breastfeeding and the practice of exclusive breastfeeding is important for the health of infants and mothers. WHO recommends exclusive breastfeeding for six months without any additional food and fluids. One form of intervention that has been carried out is an educational program given to pregnant women. The purpose of this study was to determine the effect of breastfeeding education on self-efficacy in breastfeeding and exclusive breastfeeding.Subjects and Method: This was a meta-analysis study using PRISMA flowchart guidelines. The article search process was carried out between 2011-2021 using databases from PubMed and Sciencedirect. Based on the database, there were 15 articles that met the inclusion criteria. The analysis was carried out using RevMan 5.3 software.Results: There were 15 articles that met the inclusion criteria which were analyzed using the Randomized Controlled Trial method. Based on 7 studies on the effect of education and self-efficacy, it showed that pregnant women who received breastfeeding education interventions had a self-efficacy score of 0.43 times higher than the control group (SMD= 0.43; 95% CI= 0.27 to 0.60; p< 0.001) and 8 Research on the effect of education on the practice of exclusive breastfeeding showed an increase of 2.46 times in exclusive breastfeeding compared to the control group (RR= 1.59; 95% CI= 1.40 to 1.81; p=0.020).Conclusion: Breastfeeding education programs for pregnant women affect self-efficacy in breastfeeding and exclusive breastfeeding.Keywords: breastfeeding education, pregnant woman, self-efficacy, exclusive breastfeedingCorrespondence:Annisa Nurindra Rahmadani. Faculty of Public Health, Universitas Diponegoro. Jl. Prof. Soedarto, SH., Tembalang, Semarang. Email: annisanrahmadani@gmai.com. Mobile: +6283838761325.Journal of Health Promotion and Behavior, (2022), 07(01): 42-54DOI: https://doi.org/10.26911/thejhpb.2021.07.01.05